Mitigating Accent Anxiety in Students’ Public Speaking Across Face-to-Face, Online, and Virtual Contexts - Hasim, Fiviyanti (Makassar State University, 2026)
Accent anxiety can hinder English as a Foreign Language (EFL) students’ public speaking performance, particularly when learners anticipate negative judgment, social exclusion, or reduced intelligibility. This study compared accent anxiety across three speaking contexts, face-to-face, online, and virtual, among 183 undergraduates from three universities in Makassar, Indonesia. Using a quantitative between-subjects design, participants were randomly assigned to one context and completed an oral reading task followed by the Accent Anxiety Scale (AAS). Exploratory and confirmatory factor analyses supported the three-dimensional structure of the scale, consisting of fear of negative evaluation, fear of intergroup rejection, and intelligibility concerns. Reliability coefficients for the total scale and subscales were satisfactory. One-way ANOVA showed a significant difference in anxiety across contexts, with the highest mean in the face-to-face group and the lowest mean in the virtual group. Tukey post-hoc comparisons indicated significant differences among all three groups. These findings suggest that delivery context shapes how accent anxiety is experienced and that virtual practice environments may provide a useful preparatory stage before live presentations. For pronunciation and public speaking courses, a staged sequence from virtual rehearsal to online and face-to-face performance may help reduce anxiety while maintaining communicative practice